1998
DOI: 10.2307/3587902
|View full text |Cite
|
Sign up to set email alerts
|

"Breaking Them up, Taking Them Away": ESL Students in Grade 1

Abstract: This article describes a longitudinal ethnographic research project in a Grade 1 classroom enrolling L2 learners and Anglophones. Using a community‐of‐practice perspective rarely applied in L2 research, the author examines three classroom practices that she argues contribute to the construction of L2 learners as individuals and as such reinforce traditional second language acquisition perspectives. More importantly, they serve to differentiate participants from one another and contribute to community stratific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 9 publications
8
65
0
6
Order By: Relevance
“…Such studies are sometimes more psychological in orientation (examples are Lantolf 2000; Lantolf & Thorne 2006;Swain et al 2010); sometimes they are more anthropologically-and sociologicallyfocused (Kostogriz & Tsolidis 2008;Toohey 1998Toohey , 2000Toohey & Norton 2010). The theories represent a shift from seeing learners as individually internalizing stable systems of language knowledge, to seeing them as differentially-positioned members of social and historical collectivities, using (and thus learning) language as a dynamic tool.…”
Section: Sociocultural Theories Of Language Learningmentioning
confidence: 99%
“…Such studies are sometimes more psychological in orientation (examples are Lantolf 2000; Lantolf & Thorne 2006;Swain et al 2010); sometimes they are more anthropologically-and sociologicallyfocused (Kostogriz & Tsolidis 2008;Toohey 1998Toohey , 2000Toohey & Norton 2010). The theories represent a shift from seeing learners as individually internalizing stable systems of language knowledge, to seeing them as differentially-positioned members of social and historical collectivities, using (and thus learning) language as a dynamic tool.…”
Section: Sociocultural Theories Of Language Learningmentioning
confidence: 99%
“…Other studies focused on immigrants' interactive challenges in elementary, secondary, and post-secondary classrooms in the U.S and Canada (Duff, 2002;Harklau, 2003;Kobayashi, 2003;Norton, 1995Norton, , 1997Norton, , 2000Norton & Toohey, 2001;Morita, 2000Morita, , 2004Toohey, 1998). These studies showed the significance of second language speaking and writing strategies, and scaffolding and peer feedback in new academic communities.…”
Section: Second Language Socializationmentioning
confidence: 99%
“…Though some researches have also shown that not all newcomers succeed in becoming legitimate participants in the new community (Norton, 2001;Toohey, 1998), Victoria's experience stands as one fortunate case. Considering these important issues on learning literacy, I conducted this particular qualitative case study in order to understand:…”
Section: Problem and Research Questionsmentioning
confidence: 99%
“…For instance, Toohey (1998), in her study with preschoolers found that the practices in certain communities "appear in effect to prevent the increasing empowerment and active participation of some of those defined as L2 learners" and that some students "become defined as deficient and are thus systematically excluded from just those practices in which they might otherwise appropriate identities and practices of growing competence and expertise" (p. 61). Zentella (2005) claims that negative attitudes toward the ways Latinos speak English have been perpetuated in the U.S. and this has negatively affected their performance at schools and identity.…”
Section: Literature Reviewmentioning
confidence: 99%